Kinerja Profesi Konselor Menghadapi Tantangan Zaman - Hafifuddin Nur; Nur Hidayah (JURNAL KONSELING GUSJIGANG, 2019)
Aim was written it this article approve is to to explain it how is counselor’s performance professional in to face challenging of era in century 21. this era challenging be marked with its many counseli who enthuse the serving to get to through technology than according to face to face, besides that still existence konseli that konselor's have consider as police school, counseli very shy to make closer to counselor, counseli doesn't know what is that counseling, they have consider  that counseling guiden's teacher to handle counselee problem ones just and counseli also don't exploit it  if not be called. to answer to this matter konselor must to control some matters related with: (1) drafted work counselling, (2) professionalism, (3) professionalization, (4) enableness, (5) entrepreneur's soul, (6) skilfulness and quality personal that effective.